KELAYAKAN BUKU SAKU SEBAGAI MEDIA PEMBELAJARAN SUBMATERI MANFAAT KEANEKARAGAMAN HAYATI - Sinaga, Yuslaina; -, Syamswisna; Wahyuni, Eko Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
This study aims to determine the feasibility of a pocket book as a learning medium for the sub-topic of the benefits of biodiversity. A descriptive qualitative approach was employed. The developed pocket book was validated by five experts, consisting of two biology lecturers from the Faculty of Teacher Training and Education at Tanjungpura University, one of a biology teachers from SMA Negeri 1 Tigalingga, one of a biology teachers from SMA Swasta Nusantara Tigalingga, and one of a biology teachers from SMA Negeri 7 Pontianak. Data analysis was carried out using the Content Validity Ratio (CVR) by Lawshe (1975). The results showed that the CVR and Content Validity Index (CVI) obtained was 0.99, indicating a very valid category. These findings suggest that the developed pocket book is feasible to be used as a learning medium for biodiversity materials and has the potential to enhance students"™ understanding of the benefits of biodiversity through concise, systematic, and easy-tounderstand content presentation.